Hematologic Malignancies Patients Face High Symptom Burden and Are Lately Referred to Palliative Consultation: Analysis of a Single Center Experience. (July 2023) - Ebert, Raissa P. C.; Magnus, Mariana M.; Toro, Pedro; Manoel, Fabiana G.; Costa, Fernando F.; Olalla Saad, Sara T.; de Melo Campos, Paula
Although hematologic neoplasms have been on the vanguard of cancer therapies that led to notable advances in therapeutic efficacy, many patients face significant symptom burden, which make them eligible for early palliative care (PC) integration. However, previous reports demonstrated that hematological malignancies receive more aggressive care at the end-of-life and are less likely to receive care from specialist palliative services compared to solid tumors. Our aim was to characterize symptom burden, performance status and clinical characteristics of a cohort of hematologic malignancies patients referred to PC outpatient consultation, according to their diagnosis. Fifty-nine hematological malignancies patients referred to PC consultation between January 2018 and September 2021 were included. Clinical and laboratory data were evaluated retrospectively by medical charts analysis. Patients exhibited high ESAS and reduced PPS scores at the time of PC referral. Acute leukemia and multiple myeloma patients had the highest symptom burden scores; in spite of this, median time from the first PC consultation until death was only 3 and 4 months, respectively. In conclusion, we identified that hematologic neoplasms patients are highly symptomatic and are frequently referred to PC in end stages of their disease.